The Impact of Advertising Content on Purchase Intention: The Mediating Role of Brand Awareness and Brand Image with Generation Z Moderation - Yohanes Ferry Cahaya; Alloysius Pamurda Dhika Mahendra; Herni Pujiati; Ilham Nawang Armanda (STIE Tri Bhakti, 2026)
This study examines the influence of advertising content on purchase intention among 500 consumers in Jakarta, Indonesia, focusing on Generation Z as a moderating factor. Employing Partial Least Squares Structural Equation Modeling (PLS-SEM), we investigate the mediating roles of brand awareness and brand image in the advertising- purchase intention relationship. Results demonstrate that advertising content significantly affects purchase intention both directly and indirectly through brand awareness and brand image. Generation Z membership significantly moderates these relationships, amplifying the effects of advertising content on brand outcomes. These findings contribute to advertising effectiveness theory and provide actionable insights for marketers targeting digitally- native consumers in emerging markets. The comprehensive model explains substantial variance in purchase intention, offering practical implications for developing generation-specific marketing strategies.